2022
DOI: 10.1021/acsmaterialslett.2c00317
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Defect Suppression of Micrometer-Thick Perovskite Single Crystals Enables Stable Photovoltaics

Abstract: Metal halide perovskite single crystals have become emerging candidates for photovoltaic applications due to their better optoelectronic properties and higher stability than their polycrystalline thin-film counterparts. However, in contrast to the rapid enhancement of power conversion efficiency (PCE), the operational stability of single-crystal perovskite solar cells (PSCs) remains far lagging behind. Herein, it is discovered that widely investigated 20 μm-thick single-crystal PSCs show poor operational stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…This value approaches the mobilities obtained in these MAPbI 3 single crystals. 85,86 It was reported in another study that orientationally pure crystalline (OPC) perovskite films with a strong orientational preference to the (112) and ( 200) planes can be fabricated through a temperature-gradient-assisted solidification process; the field-effect transistor (FET) devices based on these OPC films show giant anisotropy in field-effect charge mobility when characterized in different directions. 87 These results confirm the orientation-dependent charge transport properties of tetragonal MAPbI 3 thin films.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…This value approaches the mobilities obtained in these MAPbI 3 single crystals. 85,86 It was reported in another study that orientationally pure crystalline (OPC) perovskite films with a strong orientational preference to the (112) and ( 200) planes can be fabricated through a temperature-gradient-assisted solidification process; the field-effect transistor (FET) devices based on these OPC films show giant anisotropy in field-effect charge mobility when characterized in different directions. 87 These results confirm the orientation-dependent charge transport properties of tetragonal MAPbI 3 thin films.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…Methylammonium lead iodide (MAPbI 3 ) single crystals (SCs) have been reported as a star semiconductor material in the perovskite family owing to their large optical absorption coefficient, excellent optoelectronic properties and accessible solution preparation, which attracts significant focus devoted to MAPbI 3 -based photodetectors and other optoelectronic devices. 17–23 For example, Huang and co-works reported that the diffusion length of MAPbI 3 SC is up to 175 μm under 1 sun illumination, leading to a high responsivity of 35 mA W −1 . Moreover, this device exhibited a peak value of external quantum efficiency at the NIR region (810 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Irreversible chemical reactions between the metal electrode and perovskite layer can appear and can deteriorate perovskite film and adjacent layers. For instance, metal ions from the electrode can diffuse to the perovskite layer under reverse bias, resulting in deep-level defects in the perovskite layer and undesirable S-shape curves in performance test [12][13][14][15]. For the PSCs under light irradiation and the electric field, iodine ions can diffuse toward the metal electrode, leaving iodine vacancy defects in the perovskite [16,17].…”
Section: Introductionmentioning
confidence: 99%